Optimizing the Simponi Application for Non-Tax State Revenue at the Rendani Class II UPBU Office - Sugiarsih, Titik; Rusdianti, Imanita Septian (Bulletin of Management and Business, 2023)
This research discusses the Optimization of the Simponi Application on Non-Tax State Revenue at the Class II Rendani UPBU Office. The study was conducted with the aim of providing an overview of activities related to Non-Tax State Revenue (PNBP) at the Class II Rendani UPBU Office. The research used a qualitative descriptive approach in the form of field research. Data sources were obtained through observations and interviews with relevant subjects, using data triangulation methodology. This method is useful for enhancing the validity and accuracy of the data obtained as precise information for analysis material. The research results showed that the Simponi Application, in general, greatly assisted in PNBP service implementation due to the presence of tutorials and guidance. The application is highly dependent on the availability of the internet network. The research results indicated that negligence occurred due to the unstable internet network; thus, network mapping and bandwidth improvement are required. Delayed payments and unrecorded receivables happened because there was a lack of specific reminders related to billing codes that were due or unpaid, necessitating special notifications when approaching the payment deadlines.